Child malnutrition and prenatal care: Evidence from three Latin American countries (2014)
Objective. To examine the effect of prenatal care (PNC) on the level and distribution of child stunting in three Andean countries-Bolivia, Colombia, and Peru-where expanding access to such care has been an explicit policy intervention to tackle child malnutrition in utero and during early childhood. Methods. An econometric analysis of cross-sectional Demographic and Health Survey (DHS) data was conducted. The analysis included ordinary least-squares (OLS) regressions, estimates of concentration curves, and decompositions of a concentration index. Results. The analysis shows that the use of PNC in Bolivia, Colombia, and Peru is only weakly associated with a reduction in the level of child malnutrition. Conclusions. Further expansion of PNC programs is unlikely to play a large role in reducing inequalities in malnutrition.